PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF VOLUNTEER ACTIVITIES WITH TEENAGERS - O. Solovyeva; L. Arutyunyan (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the consideration of opportunities for the development of volunteerism in the adolescent environment. The authors analyze the essence and advantages of volunteer activity, and pay special attention to the disclosure of its educational potential. The article highlights the measures that contribute to the development of volunteerism, justifies the need to create a system of psychological and pedagogical support for volunteer activities with adolescents. The article presents the author’s model of psychological and pedagogical support of volunteer activities, which includes targeted, methodological, substantive, procedural and effective components.